Inadvertent consequences of percutaneous coronary intervention to treat unstable spontaneous coronary artery dissection. Issue 3 (September 2015) - Taguchi, Eiji; Nakao, Koichi; Kogure, Tomohito; Suzuyama, Hiroto; Inoue, Masayuki; Kodama, Kazuhisa; Yoshida, Masayoshi; Miyamoto, Shinzo; Sakamoto, Tomohiro
Abstract: We present two cases of spontaneous coronary artery dissection (SCAD), which were diagnosed and treated with emergent percutaneous coronary intervention (PCI). Patients with ongoing ischemia due to SCAD need emergent coronary revascularization with PCI or coronary artery bypass grafting. We discuss the difficulties of PCI to bail out unstable SCAD regardless of the modern techniques and modalities. Brief reviews of the literature with relevance are included. <Learning objective: We should probably pay more careful attention to perform PCI for unstable SCAD because of the fragileness of the dissected vessels.>